Young Customer’s Green Purchase Intention: Study From Developing Country, Indonesia - Fitriana, Ana (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This study aims to test and analyze the effects of green product knowledge, green product awareness, green product interest, and perceived green value as intervening variables on green purchase intention in Indonesia. Reformulation The method used in this study is a quantitative method using online distribution of questionnaires The sample of this study is 215 young Indonesian customers with knowledge about eco-friendly products. It consists of specifically targeted sampling processed using AMOS 22 analytical tools and Structural Equation Modeling (SEM) survey techniques, the findings of this study show that our young customers have high green product knowledge, high environmental awareness, and green values ​​related to green purchase intentions. It shows that you have an awareness of Otherwise, all hypotheses are accepted